HBM4EU-MOM: Prenatal methylmercury-exposure control in five countries through suitable dietary advice for pregnancy – Study design and characteristics of participants - Iavicoli I.; Leso V. (International Journal of Hygiene and Environmental Health, 2023)
Background: Seafood is a major source of vital nutrients for optimal fetal growth, but at the same time is the main source of exposure to methylmercury (MeHg), an established neurodevelopmental toxicant. Pregnant women must be provided with dietary advice so as to include safely fish in their diet for nutrition and mercury control. The aim of this work is to present the design of a multicentre randomized control trial (RCT), which combines human biomonitoring (HBM) with dietary interventions using seafood consumption advice to pregnant women for MeHg control, and to collect information about other possible sources of exposure to mercury. It also presents the materials developed for the implementation of the study and the characteristics of the study participants, which were self-reported in the first trimester of pregnancy. Methods: The “HBM4EU-MOM” RCT was performed in the frame of the European Human Biomonitoring Initiative (HBM4EU) in five coastal, high fish-consuming European countries (Cyprus, Greece, Spain, Portugal and Iceland). According to the study design, pregnant women (≥120/country, ≤20 weeks gestational age) provided a hair sample for total mercury assessment (THg) and personal information relevant to the study (e.g., lifestyle, pregnancy status, diet before and during the pregnancy, information on seafood and factors related to possible non-dietary exposures to mercury) during the first trimester of pregnancy. After sampling, participants were randomly assigned to “control” (habitual practices) or “intervention” (received the harmonized HBM4EU-MOM dietary advice for fish consumption during the pregnancy and were encouraged to follow it). Around child delivery, participants provided a second hair sample and completed another tailored questionnaire. Results: A total of 654 women aged 18–45 years were recruited in 2021 in the five countries, primarily through their health-care providers. The pre-pregnancy BMI of the participants ranged from underweight to obese, but was on average within the healthy ...